Madrasah Education Quality Reform: Improving Teacher Quality post Pandemic in Indonesia - Arif Rahman; Mohd Izzuddin Mohd Pisol; Maya Novita Sari; Zalik Nuryana (AL-ISHLAH: Jurnal Pendidikan, 2024)
Indonesia has launched a reform agenda for the quality of madrasah education through the Ministry of Religious Affairs of the Republic of Indonesia, especially in terms of improving the quality of madrasah teachers as part of the sustainable development carried out by the government in the field of education. Therefore, this research aims to highlight the factors underlying the reform agenda on teacher quality. In addition, how madrasahs take the momentum of the end of the pandemic as a turning point to make comprehensive improvements. This research uses a qualitative research paradigm with a literature approach, where data is collected from the study of various literature related to the topic of discussion. The data is then verified and analyzed systematically to be presented in a structured manner. The results show that there are at least three main factors that encourage madrasahs to reform the quality of teachers related to aspects of digitalization, adaptation, and creativity. These three aspects are the core competencies that are relevant for madrasah teachers to face various situations today. The digitalization aspect departs from teachers' low teaching technology skills when implementing online classes and using various alternative learning technologies. The adaptive aspect is how the teacher's ability to respond to uncertain changes, where the rapid transition of situations requires teachers' attitude and ability to adapt to various situations. The creativity aspect for teachers is the ability of teaching art that is needed for teachers to create a pleasant learning atmosphere for students both during online and offline learning.